The Routledge companion to religion and science - Haag, James W.; Peterson, Gregory R. , 1966-; Spezio, Michael L. (Routledge, 2012)
The field of religion and science is one of the most exciting and dynamic areas of research today. This Companion brings together an outstanding team of scholars to explore the ways in which science intersects with the major religions of the world and religious naturalism. The collection provides an overview of the field and also indicates ways in which it is developing. Each topic is presented in a clear readable fashion, ideal for scholars but also useful for upper level undergraduates